2014
DOI: 10.2478/pjvs-2014-0082
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the occurrence of Chronic Superficial Keratitis in 308 German Shepherd dogs: 1999-2010

Abstract: Chronic Superficial Keratitis (CSK) is an autoimmune mediated inflammation of the cornea, that is usually bilateral but often with nonsymmetrical manifestation.The aim of this study was to determine the occurrence and appearance of clinical symptoms of CSK in German Shepherd dogs in Poland and Slovakia.CSK was diagnosed in 308 German Shepherds for a period of 11 years (from 1999 to 2010). The highest incidence of the CSK (p < 0.001) in Slovakia and in Poland was in dogs between the ages of 5-8 years. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Corneal cytology revealed no signs of neoplasia. Instead, the epithelial phenotype resulting from this ocular surface evaluation demonstrated noncorneal tissue, evidenced by the presence of goblet cells commonly found in the conjunctiva 4 (data not shown).…”
Section: Laboratory Evaluationmentioning
confidence: 87%
See 1 more Smart Citation
“…Corneal cytology revealed no signs of neoplasia. Instead, the epithelial phenotype resulting from this ocular surface evaluation demonstrated noncorneal tissue, evidenced by the presence of goblet cells commonly found in the conjunctiva 4 (data not shown).…”
Section: Laboratory Evaluationmentioning
confidence: 87%
“…Chronic super cial keratitis (CSK) or Uberreiter Syndrome (1)represent a chronic, in ammatory non-ulcerative disease of the super cial corneal stroma, which causes signi cant damage and consequent visual impairment in dogs (2). This condition is particularly common in German shepherd and Greyhounds, Belgian Shepherd dogs, but other breeds may be affected (3,4) . The disease also affects humans (5) and affected dogs may serve as a model species for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology is still not fully understood but CD4+ T lymphocyte infiltration from cornea stroma suggests an immunological background [ 64 , 65 , 66 , 67 ]. The German shepherd dog is a predisposed breed, but it can also occur in the Australian shepherd, collie, border collie, golden retriever, Akita, vizsla, and others [ 62 , 68 ]. Several studies have found that excessive ultraviolet exposure increases the risk of CSK [ 62 , 69 , 70 ].…”
Section: Csa-implants In Veterinary Ophthalmologymentioning
confidence: 99%
“…A doença não é restrita à córnea e não é superficial 7 , porém é uma doença crônica, inflamatória e não ulcerativa do estroma superficial corneano, que causa danos significativos e comprometimento visual em cães 22 . Esta condição é particularmente comum em galgos, pastores alemães e pastores belgas, Greyhounds, mas outras raças também podem ser afetadas 23,24 e aparenta ter características herdáveis 25 .…”
Section: Lista De Ilustraçõesunclassified